LEGAL CERTAINTY AND CONTRACTUAL FREEDOM IN INDONESIAN CIVIL LAW: A NORMATIVE ANALYSIS OF THE PRINCIPLES OF THE CIVIL CODE AND CONTEMPORARY PRACTICE - Santosa, Jaka (Gapenas Publisher, 2025)
This paper examines the principles of legal certainty and contractual freedom in Indonesian civil law through a normative juridical analysis of the Civil Code and its application in contemporary practice. Legal certainty ensures predictability and enforceability of agreements, while contractual freedom provides parties with autonomy to establish contractual terms. However, these principles are not absolute and often exist in tension, particularly when contractual autonomy is restricted by statutory provisions, public order, morality, or consumer protection laws. By analyzing statutory frameworks, jurisprudence, and doctrinal perspectives, this study finds that Indonesian civil law seeks to harmonize these principles rather than treat them as opposites. Contemporary challenges, such as standard form contracts, digital transactions, and consumer protection, highlight the need for a balanced approach. The findings demonstrate that Indonesian civil law must uphold both legal certainty and contractual freedom in a way that respects individual autonomy while safeguarding justice, fairness, and social interests.